Creating a Bi-Directional Source-to-Source Compiler Using MDE Transformation Techniques: A Proof-of-Concept Using the General-Purpose Programming - Blomberg, Sebastian; Severin, Joel (My University, 2017)
In this thesis, we discuss how a bidirectional source-to-source compiler, for the declarative general-purpose languages COBOL and C++, can be implemented using Model-Driven Engineering (MDE) tools and practices. The outcome of our work is primarily an approach for implementing said bidirectional compiler using formal grammars, bidirectional transformation languages, and a developed concept model. This approach also illustrates how a programmer’s intent can be transferred between languages. In order to evaluate the approach, a prototype was realized using Ecore, Xtext, and Medini QVT. In the process, a library for emulation of COBOL data types in C++ was also developed. Finally, we conclude the success of the developed approach and prototype.
Keywords: Data- och informationsvetenskap; Computer and Information Science